Magnetic and structural properties of Fe-implanted GaN at room temperature. (February 2021) - Li, Bingsheng; Peng, Dingping; Li, Junhan; Kang, Long; Zhang, Tongmin; Zhang, Zhenxing; Jin, Shuoxue; Cao, Xingzhong; Liu, Jihong; Wu, Lu; Wang, Xu; Fang, Zhongqiang; et al.
Abstract: GaN grown by metal-organic chemical vapour deposition on the sapphire substrate was implanted with 3 MeV Fe 10+ ions to fluences of 1 × 10 13 to 5 × 10 15 ions/cm 2 at room temperature. The change of magnetic property with the implantation fluence was measured by vibrating sample magnetometer. The structural features, including implantation-induced interstitials and vacancies, were studied by a combination of Raman spectroscopy, photoluminescence spectroscopy, transmission electron microscopy and positron annihilation technology. The ferromagnetic behaviour was observed in the as-grown sample, and the saturation magnetization reached the maximum after the Fe implantation to a fluence of 5× 10 13 ions/cm 2 . With increasing fluence, it decreased to be even smaller than that of the as-grown sample. The possible reasons are discussed. Highlights: Magnetic and structural properties of Fe-implanted GaN were investigated. . The N vacancies and dislocations can retard the Fe activation at Ga sites. Defect annealing would improve the saturation magnetization of Fe-implanted GaN.